Research priorities to support evidence-informed policies and advocacy for access to safe abortion care in sub-Saharan Africa. Issue 1 (1st January 2021) - Ajayi, Anthony Idowu; Ouedraogo, Ramatou; Juma, Kenneth; Kibunja, Grace; Cheruiyot, Collins; Mwoka, Meggie; Igonya, Emmy Kageha; Opondo, Winnie; Otukpa, Emmanuel; Kabiru, Caroline W.; Ushie, Boniface Ayanbekongshie
Abstract: A key obstacle to advocacy efforts to promote legal and policy reforms that ensure women's and girls' access to comprehensive abortion care (CAC) is the lack of relevant and timely evidence. This commentary outlines a research agenda-setting initiative that identified research priorities to support evidence-informed policy and advocacy for CAC access in sub-Saharan Africa (SSA). It involved three phases: 1) a landscape analysis; 2) research agenda co-creation with stakeholders, and 3) a validation exercise on research priorities. Overall, the priority evidence needs included 1) estimating the incidence and magnitude of unsafe abortion and related costs; 2) examining the role of abortion laws and policies in facilitating or inhibiting access to CAC; 3) developing and documenting successful approaches for addressing societal barriers to the provision of CAC, and fostering a more inclusive and liberal abortion environment, and 4) documenting practice-based evidence on the provision of legal abortion services as well as for advocating for CAC. Various stakeholders, including researchers, policymakers, civil society organizations, and funding agencies, will find the agenda useful as they engage, at different levels, for the full domestication and implementation of forward-looking commitments on access to CAC in SSA.